2012
DOI: 10.1371/journal.pone.0050120
|View full text |Cite
|
Sign up to set email alerts
|

Clarifying the Role of the Rostral dmPFC/dACC in Fear/Anxiety: Learning, Appraisal or Expression?

Abstract: Recent studies have begun to carve out a specific role for the rostral part of the dorsal medial prefrontal cortex (dmPFC) and adjacent dorsal anterior cingulate cortex (dACC) in fear/anxiety. Within a novel general framework of dorsal mPFC/ACC areas subserving the appraisal of threat and concomitant expression of fear responses and ventral mPFC/ACC areas subserving fear regulation, the rostral dmPFC/dACC has been proposed to specifically mediate the conscious, negative appraisal of threat situations including… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
47
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(52 citation statements)
references
References 35 publications
5
47
0
Order By: Relevance
“…Although our data cannot provide evidence for a causal influence of dACC on pupil responses, we propose that at least part of this association could be explained by threat appraisal, which has been related to dACC activity in previous work (Etkin, Egner, & Kalisch, 2011;Maier et al, 2012;Mechias, Etkin, & Kalisch, 2010). In line with this, we found that pupil dilations in response to CS+ appear most robustly seconds after stimulus onset, just before US administration.…”
Section: Fear Conditioningsupporting
confidence: 84%
“…Although our data cannot provide evidence for a causal influence of dACC on pupil responses, we propose that at least part of this association could be explained by threat appraisal, which has been related to dACC activity in previous work (Etkin, Egner, & Kalisch, 2011;Maier et al, 2012;Mechias, Etkin, & Kalisch, 2010). In line with this, we found that pupil dilations in response to CS+ appear most robustly seconds after stimulus onset, just before US administration.…”
Section: Fear Conditioningsupporting
confidence: 84%
“…Fear conditioning or the expression of conditioned fear in healthy humans has been associated with activity in medial prefrontal brain regions such as dACC and vmPFC (Alvarez et al, 2008; Buchel et al, 1999; Buchel et al, 1998; Klucken et al, 2009; LaBar et al, 1998; Lang et al, 2009; Maier et al, 2012; Marschner, Kalisch, Vervliet, Vansteenwegen, & Buchel, 2008; Milad, Quirk, et al, 2007; Milad, Wright, et al, 2007; Morris & Dolan, 2004; Phelps, Delgado, Nearing, & LeDoux, 2004). SCRs during conditioning are correlated with fMRI response in dACC and dACC thickness (Milad, Quirk, et al, 2007), and with the rate of resting metabolism in dACC (Linnman et al, 2013).…”
Section: 1 Fear Conditioning and Extinction In Healthy Humansmentioning
confidence: 99%
“…As instructed and uninstructed conditioning might tap different processes, this may translate into different behavioral and neural correlates (Mechias et al 2010;Maier et al 2012).…”
Section: Instruction Vs Noninstructionmentioning
confidence: 99%